Identifying social entrepreneurship competencies of managers in social entrepreneurship organizations in healthcare sector - Zahra Amini; Zahra Arasti; Afsaneh Bagheri (Journal of Global Entrepreneurship Research, 2018)
In spite of paying much attention to social entrepreneurship in academia, such is not the case in social entrepreneurship organizations. Although to fulfill economic and social missions, managers are required to possess economic and social competencies, only few studies investigated this important subject. The present study aims to identify the social entrepreneurship competencies of managers in social entrepreneurship organizations in the field of healthcare. Purposive sampling was used in the population of managers of social entrepreneurship organizations in the field of treatment and prevention of specific diseases (such as cancer, MS, thalassemia, etc.) and also social entrepreneurship organizations in the field of treatment and empowerment of the disabled. Eight managers in this field were interviewed and data was analyzed by open and axial coding using ATLAS.ti software. In total, 42 competencies have been identified in 10 categories and 5 main dimensions including communication competencies, personal competencies, managerial competencies, social competencies and health professional entrepreneurial competencies.
Keywords: 650; Social entrepreneurship; Competency Social entrepreneurial competency; Entrepreneurial organizations